EVALUASI KUALITAS WEBSITE PEMESANAN ONLINE LABORATORIUM IOT X-CAMP PT. XL AXIATA MENGGUNAKAN METODE WEBQUAL 4.0 - Roelly Hoemdiana (Jurnal Informatika dan Bisnis, 2021)
The quality of a website becomes an important factor that must be considered in a company. To find out the quality of a website it is necessary to measure the quality of the website based on its users. This study aims to find out how the quality of the online ordering website of the IoT X-Camp Laboratory PT. XL Axiata. This study evaluates the quality of websites using the Webqual 4.0 method which consists of 3 variables, usability quality, information quality, and service interaction quality. The analysis technique used is descriptive analysis that will provide an overview of the indicators that need improvement or need to be maintained based on user perception. This research uses a quantitative approach by distributing questionnaires to website users, especially people who know IoT. The results of descriptive analysis of web site respondents based on usability have an average value of 3.90 with a response rate of 76.43%, an information quality with an average of 3.81 with an achievement level of respondents 76.13 and the quality of service interactions with an average of 3 ,78 with 75.68% achievement rate of respondents. The conclusion of this study states that the scores of all variables in each indicator are quite good. This shows that the quality of the website is not entirely in accordance with the wishes of the user. Keywords : Website Quality, Webqual 4.0, Usability, Information Quality, Service Interaction Quality.